Application On Payment UPS Online For Students Android-Based National University Information System: Application On Payment UPS Online For Students Android-Based National University Information System - Fikrianzi Nindyo Kusumo; Agung Triayudi; Riad Sahara (Jurnal Mantik, 2020)
In every educational institution, it certainly has its own tuition payment system. Along with the rapid advancement of technology and information at this time, certainly needed an effective and efficient and relevant system which will make these institutions can compete with other institutions. At the National University lecture payment and verification of lecture payments are still done conventionally, ie students make transfers or cash deposits to the Bank in collaboration with the campus, then students need to show proof of physical payment to campus staff (BAK) for verification which is assessed less efficient. With these problems, the author in his research intends to design an online UPS payment application based on Android and integrated with the Midtrans API. Midtrans API is used to improve payment service performance and make it easier for students to make UPS payments on mobile. In this research, several types of programming languages are used, including PHP, Java, and MySQL, accompanied by the use of the waterfall method. The Waterfall method is used as a system development method which is carried out systematically, starting from planning to testing the system. The reason the author uses the waterfall method is that it can facilitate the management and design requirements (needs) of the system created. With this research the author hopes to produce convenience for students in making payments to UPS verification through an online UPS payment application.